The Analysis of Work Motivation in The General Affair Division of PT. Kornet Logistic - Sultan Salahuddin Al Ayyubi; Christian Wiradendi Wolor; Marsofiyati, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study aims to analyze and propose solutions related to the work motivation of employees of the General Department of PT Kornet Logistic and improve the work motivation of employees, a company operating in the logistics sector. The preliminary results of this study show that the main problem in motivating employees is dissatisfaction with the salary they receive. When employees feel that the salary or wages, they receive are not enough to meet their family or personal needs, this causes their work motivation to decrease or weaken and slows down the overall productivity of the company. This study uses a descriptive qualitative method. by collecting data through interviews with four managers, direct observations in the company and documents on the company environment that have a relationship with employee work motivation. This study used a purposive sampling method to select interviewees, starting with the first employee interviewed, who then introduced the next interviewee in the form of their co-workers. Employee motivation is also influenced by both internal and external factors. Internal factors include the desire for achievement and recognition, while external factors relate to pay or treatment as well as relationships with co-workers and managers. Based on comparisons with previous research, work motivation consistently has a positive and significant impact on productivity, job performance, and discipline. This study provides insights into work motivation and the importance of its role in business.